Germany and the confessional divide religious tensions and political culture, 1871-1989 - Ruff, Mark Edward 1969-; Großbölting, Thomas 1969-2025 (Berghahn, 2022)
"From German unification in 1871 through the early 1960s, confessional tensions between Catholics and Protestants were a source of deep division in German society. Engaging this period of historic strife, Germany and the Confessional Divide focuses on three traumatic episodes: the Kulturkampf waged against the Catholic Church in the 1870s, the collapse of the Hohenzollern monarchy and state-supported Protestantism after World War I, and the Nazi persecution of the churches. It argues that memories of these traumatic experiences regularly reignited confessional tensions. Only as German society became increasingly secular did these memories fade and tensions ease"
Keywords: Katholische Kirche; Geschichte 1871-1989; Evangelische Kirche; Konfessionalität; Gesellschaft; Deutschland; Germany / Church history / 19th century; Germany / Church history / 20th century; Catholic Church / Relations / Protestant churches / History; Protestant churches / Relations / History; Christianity and politics / Germany / History; Church and state / Germany / History; Catholic Church; Christianity and politics; Church and state; Interfaith relations; Protestant churches; Germany; 1800-1999; Church history; History; Aufsatzsammlung